Internalisasi Solidaritas Sosial dan Nilai-Nilai Islam melalui Tradisi Weweh - Ardian Al Hidaya (Journal of Economics, Law, and Humanities, 2023)
Weweh is a hereditary tradition that is still practiced by the community, especially in Java, by delivering food to relatives ahead of Eid al-Fitr. Qualitative research with an ethnographic approach aims to describe how the weweh tradition contributes to maintaining and encouraging social solidarity among the community and how this role is related to Islamic values in Sawahan Village, Sawahan Sub-district, Madiun Regency. The results show that weweh is usually performed after the night of 21 Ramadan until the day before Eid. There has been a modification of the food (wewehan) given for weweh from processed food consisting of rice, various vegetables, and side dishes such as opor and roast chicken arranged in rantang susun to gifts or parcels consisting of raw food ingredients such as cooking oil, sugar, coffee, tea, candy, biscuits, pastries, and instant noodles. Children of younger relatives are usually the ones who deliver the gifts to the homes of the older relatives who are given wewehan. The relatives who receive the wewehan usually give the money and or food back in the giving container. The weweh tradition teaches generosity through food alms, friendship, maintaining cultural heritage, strengthening a sense of kinship and social solidarity, and is able to provide a sense of happiness for the giver and recipient of wewehan, especially if the wewehan recipient is a poor person who will be helped by the presence of food or food ingredients to welcome the Eid celebration. It is proven that this weweh tradition impacts the internalization of social solidarity with the content of Islamic values in the community.